On Optimality Conditions for Henig Efficiency and Superefficiency in Vector Equilibrium Problems. (10th December 2018) - Luu, Do Van; Mai, Tran Thi
Abstract: Necessary optimality conditions for local Henig efficient and superefficient solutions of vector equilibrium problems involving equality, inequality, and set constraints in Banach space with locally Lipschitz functions are established under a suitable constraint qualification via the Michel–Penot subdifferentials. With assumptions on generalized convexity, necessary conditions for Henig efficiency and superefficiency become sufficient ones. Some applications to vector variational inequalities and vector optimization problems are given as well.